Drug resistance and treatment failure in leishmaniasis: A 21st century challenge. - Alicia Ponte-Sucre; Francisco Gamarro; Jean-Claude Dujardin; Michael P Barrett; Rogelio López-Vélez; Raquel García-Hernández; Andrew W Pountain; Roy Mwenechanya; Barbara Papadopoulou (Public Library of Science (PLoS), 2017)
Reevaluation of treatment guidelines for Old and New World leishmaniasis is urgently needed on a global basis because treatment failure is an increasing problem. Drug resistance is a fundamental determinant of treatment failure, although other factors also contribute to this phenomenon, including the global HIV/AIDS epidemic with its accompanying impact on the immune system. Pentavalent antimonials have been used successfully worldwide for the treatment of leishmaniasis since the first half of the 20th century, but the last 10 to 20 years have witnessed an increase in clinical resistance, e.g., in North Bihar in India. In this review, we discuss the meaning of "resistance" related to leishmaniasis and discuss its molecular epidemiology, particularly for Leishmania donovani that causes visceral leishmaniasis. We also discuss how resistance can affect drug combination therapies. Molecular mechanisms known to contribute to resistance to antimonials, amphotericin B, and miltefosine are also outlined.